2012
DOI: 10.3390/su4061292
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Environmental Management Systems on Source Separation in the Work and Home Settings

Abstract: Abstract:Measures that challenge the generation of waste are needed to address the global problem of the increasing volumes of waste that are generated in both private homes and workplaces. Source separation at the workplace is commonly implemented by environmental management systems (EMS). In the present study, the relationship between source separation at work and at home was investigated. A questionnaire that maps psychological and behavioural predictors of source separation was distributed to employees at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 23 publications
0
22
0
1
Order By: Relevance
“…Green employees shape their environmental beliefs and behaviors both in their private life [79] and in their work context [80]. Muster and Schrader [81] describe the reciprocal interactions between private and work domains as a cycle of "green work-life balance".…”
Section: Green Identitymentioning
confidence: 99%
“…Green employees shape their environmental beliefs and behaviors both in their private life [79] and in their work context [80]. Muster and Schrader [81] describe the reciprocal interactions between private and work domains as a cycle of "green work-life balance".…”
Section: Green Identitymentioning
confidence: 99%
“…En spridningseffekt har påvisats mellan källsortering av avfall på arbetsplatsen och att återvinna mer hemma (Andersson, Eriksson et al 2012). Den här studien har visat att ett enda beteende -källsortering -kan spilla över mellan olika omgivningar.…”
Section: Att Skingra Mytenunclassified
“…A spill-over effect has been demonstrated between source separation of waste in the workplace and recycling more at home (Andersson, Eriksson et al 2012). A recent Swedish study (Andersson et al 2012) has shown that a single behaviour -source separation -can spill over between different settings: those who recycled less at home increased their household recycling once an environmental management system was adopted in their workplace or spill-over can occur where activities are similar (e.g.…”
Section: Dispelling the Mythmentioning
confidence: 99%
“…A recent Swedish study (Andersson et al 2012) has shown that a single behaviour -source separation -can spill over between different settings: those who recycled less at home increased their household recycling once an environmental management system was adopted in their workplace or spill-over can occur where activities are similar (e.g. choosing organic products can spill-over into choosing fair trade products) and a single activity can spill-over from one context to another (e.g.…”
Section: Dispelling the Mythmentioning
confidence: 99%